The Influence of Accounting Information Systems and Reporting Finance of Management Control - Raden Wulan Saparinda; Tita Partyar; Fitril Aqilah (DPPM Universitas Pelita Bangsa, 2023)
The accounting information system is tasked with providing information needed for supervision and action on the assessment of management control.The purpose of this study is to find out and obtain empirical evidence about the effect of accounting information systems and financial reporting on management control (study on construction service companies registered with the Gapensi Association of Majalengka Regency in 2021).This study uses quantitative data. The population in this study is a construction service company registered with the Gapensi Association of Majalengka Regency in 2021. The sample selection in this study used the saturated sampling method, meaning that the entire population associated with this research variable was sampled. With data collection techniques using questionnaires. The design of data analysis used descriptive analysis and verification analysis using SPSS version 21.0 program. The results of this study indicate that the accounting information system has a significant effect on management control, and financial reporting has a significant effect on management control.